Grower adoption of insecticide resistance management practices increase with extension‐based program. Issue 2 (19th September 2018) - Leach, Ashley B; Hoepting, Christine A; Nault, Brian A
Abstract: BACKGROUND: Insecticide resistance management (IRM) practices that improve the sustainability of agricultural production systems are developed, but few studies address the challenges with their implementation and success rates of adoption. This study examined the effectiveness of a voluntary, extension‐based program to increase grower adoption of IRM practices for onion thrips ( Thrips tabaci ) in onion. The program sought to increase the use of two important IRM practices: rotating classes of insecticides during the growing season and applying insecticides following an action threshold. RESULTS: Onion growers ( n  = 17) increased their adoption of both IRM practices over the 3‐year study. Growers increased use of insecticide class rotation from 76% to 100% and use of the action threshold for determining whether to apply insecticides from 57% to 82%. Growers who always used action thresholds successfully controlled onion thrips infestations, applied significantly fewer insecticide applications (one to four fewer applications) and spent $148/ha less on insecticides compared with growers who rarely used the action threshold. Growers who regularly used action thresholds and rotated insecticide classes did so because they were primarily concerned about insecticide resistance development in thrips populations. CONCLUSION: Implementation of the IRM education program was successful, as adoption rates of both practices increased within 3 years. Growers were surprisingly most receptive to adopting these practices to mitigate insecticide resistance as opposed to saving money. Developing extension‐based programs that involve regular and interactive meetings with growers may significantly increase the adoption of IRM and related integrated pest management tactics. © 2018 Society of Chemical Industry Abstract : Developing effective insecticide resistance management (IRM) programs is critical to the sustainability of agricultural production. This study examined the effectiveness of an extension‐based program to increase grower adoption of IRM practices.